ANALISIS CAMPUR KODE DALAM NOVEL BIDADARI BERMATA BENING KARYA HABIBURRAHMAN EL SHIRAZY (KAJIAN PRAGMATIK) - Erni Jera Ananggia; Ni Luh Sukanadi; I Nyoman Suparsa (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2021)
Language as a means or tool of communication owned by humans ini general to convey ideas, ideas, and information to other people. Human life cannot be separated from language because language is the mots important means of communicating every day. And the information conveyed will be well received if the speaker (speaker) and listener (opponet) both understand the language used. code mixing does not only occur in spoken from, but also occur in spoken form, but also occurs ini spoken language which is written ini the form of discourse. The problem analyzed in this study are (1) the form of interference in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy (2) the function of code mixing in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy. The purpose of research is to find out the form of code mixing in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy. The method used in this study is a descriptive method with a qualitative form, namely describing the form and function of the occurrence of code mixing contained in the novel Bidadari Bemata Bening by Habiburrahman El Shirazy. Based on data analysis in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy, it was found that there was a mix of regional language codes (Javanese) and foreign languages (Arabic and English) totaling 47 data. mixing code in the form of words, mixing in the form of phrases, mixing code in the form of repeated words, mixing code in the form of compound words or idioms. The functions behind the code mixing in the novel Bidadari with Bening eyes by Habiburrahman El Shirazy are (1) for respect, (2) to emphasize a meaning, (3) to show self-identity, and (4) because of the influence of speech.